PERBANDINGAN SENYAWA PROKSIMAT PADA DAUN TERUNG PIPIT (Solanum torvum) BERDASARKAN LOKASI TUMBUH - Nunuk Helilusiatiningsih (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2022)
Indonesia was classified as an agricultural country and the potential in agricultural cultivation includes plantation crops, horticulture, food crops and others. Eggplant plants were easy to grow and were liked by the public because of their delicious taste and high nutritional value and various types, namely Dutch eggplant, purple eggplant, sparrow eggplant and others. The purpose of the research was to study the proximate content of fresh and dried leaves, especially the sparrow eggplant found in the Mojokerto area, Kediri, Malang. The research method is a quantitative chemical test with parameters such as water content, ash content, protein, fat, carbohydrates in the leaves. The results of the analysis obtained were as follows: Mojokerto Region: Fresh leaves have a moisture content of 64.29%; Ash content 3, 46%; Protein 22, 87%, Fat 4.47%; Carbohydrates 4.91%, Dried leaves: 7.51%; 12.32%; 25.46%; 3.28%, 51.43%. Kediri area, fresh leaves: 64.89%; 3, 78%,; 23.18%, 4.93%; 3.22% while dry leaves : 7.38%, 12.46%, 25.75%, 3.65%; 50.76%. Malang location fresh leaves: 65.07%; 2, 96%, 24,50%, , 5.41%; 4.46%; dry leaves : 6.70%; 7.20%, 26.80%, 4.70%, 54.58 %. So the effective growing location for sparrow eggplant is Malang because of the potential for optimal proximate content